Phyllostomid bat microbiome composition is associated to host phylogeny and feeding strategies - Carrillo-Araujo, Mario; Taş, Neslihan; Alcántara-Hernández, Rocio J.; Gaona, Osiris; Schondube, Jorge E.; Medellín, Rodrigo A.; Jansson, Janet K.; Falcón, Luisa I. (Frontiers in Microbiology, 2015)
The members of the Phyllostomidae, the New-World leaf-nosed family of bats, show a remarkable evolutionary diversification of dietary strategies including insectivory, as the ancestral trait, followed by appearance of carnivory and plant-based diets such as nectarivory and frugivory. Here we explore the microbiome composition of different feeding specialists: insectivore Macrotus waterhousii, sanguivore Desmodus rotundus, nectarivores Leptonycteris yerbabuenae and Glossophaga soricina, and frugivores Carollia perspicillata and Artibeus jamaicensis. The V4 region of the 16S rRNA gene from three intestinal regions of three individuals per species was amplified and community composition and structure was analyzed with α and β diversity metrics. Bats with plant-based diets had low diversity microbiomes, whereas the sanguivore D. rotundus and insectivore M. waterhousii had the most diverse microbiomes. There were no significant differences in microbiome composition between different intestine regions within each individual. Plant-based feeders showed less specificity in their microbiome compositions, whereas animal-based specialists, although more diverse overall, showed a more clustered arrangement of their intestinal bacterial components. The main characteristics defining microbiome composition in phyllostomids were species and feeding strategy. This study shows how differences in feeding strategies contributed to the development of different intestinal microbiomes in Phyllostomidae.